The Perception of Binus University Chinese Speaking Teachers Towards The Speaking Test Questions - Yetty Yetty (Bina Nusantara University, 2012)
In relation to teaching and learning language, speaking always becomes an important skill. Speaking lesson has been designed as the main course in foreign language teaching and teachers have to master the teaching method in class, and he must be able to design a standard speaking test to assess student capability in speaking. In this article, the writer uses the theory of standard speaking test design, and combines it with the result of interview with three speaking teachers of the Chinese Department, BINUS University. This is to analyze the speaking test design and content. The result of the analysis shows that the important parts in speaking test design are reading, questions and answers, and the narration. It is used to assess student’s expression, communication, and the level of phonetic abilities For the test content, the three teachers think that the material must be studied before and it is also possible to use small part from other materials outside the textbook.